Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/jsa.0b013e318270d1bd
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of OA of the Knee in the Middle-aged Athlete

Abstract: Knee arthroscopy for patients with osteoarthritis remains controversial. The outcome of arthroscopic debridement in a patient with symptomatic arthritis, and in the absence of mechanical symptoms, is inconsistent and short lived. However, in carefully selected patients with mild or moderate arthritis on standing radiographs, with the acute onset of symptoms, well-localized joint line pain, and painful mechanical symptoms, improved knee function can be expected. Regardless, the natural history of the disease pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 47 publications
0
21
0
2
Order By: Relevance
“…A common treatment for these lesions is microfracture (MFX) due to the minimally invasive approach, costeffectiveness, and technical simplicity. [4][5][6] The optimal indication is a young, active patient (<40 years old) with a smaller lesion (<2 to 3 cm 2 ). 7 The resultant repair tissue is primarily fibrocartilage, which has been shown to be biomechanically inferior to hyaline articular cartilage.…”
mentioning
confidence: 99%
“…A common treatment for these lesions is microfracture (MFX) due to the minimally invasive approach, costeffectiveness, and technical simplicity. [4][5][6] The optimal indication is a young, active patient (<40 years old) with a smaller lesion (<2 to 3 cm 2 ). 7 The resultant repair tissue is primarily fibrocartilage, which has been shown to be biomechanically inferior to hyaline articular cartilage.…”
mentioning
confidence: 99%
“…The use of arthroscopy as a treatment for knee osteoarthritis is contentious with opposing sets of literature. 2,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Recent publications from NICE guidelines toward restricting its use and other pressures have developed to deter the surgeon from offering this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in Aichroth's 16,17 prospective review of 254 patients treated by arthroscopic knee debridement, 85% of the patients were satisfied with the treatment and 75% of the knees gave minimal discomfort with improved function after surgery. The average follow-up for these patients was 44 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroscopic chondroplasty can theoretically help remove inflammatory mediators, mechanical cartilage fragments, and loose bodies, and some studies have shown short-term relief for a 2-year period. [10][11][12] Other studies evaluating arthroscopic treatment have demonstrated questionable results. 13,14 Advancements in cartilage restoration and arthroplasty techniques have led to improved outcomes following more invasive surgical interventions.…”
Section: Introductionmentioning
confidence: 99%